Nauka w służbie wiary, czyli ile można zdziałać ad maiorem Dei gloriam. O wydanych i niewydanych pracach naukowych Michała Boyma SI - Miazek-Męczyńska, Monika (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Looking at an interesting and very diverse scientific out-put of Michael Boym, Polish jesuit missionary in China, one can ask why so many of his works still remain unpublished. This text analyses some circumstances and conditions that impacted this situation for example relation between Boym and two other Jesuits – Martino Martini and Athanasius Kircher, complicated political situation of the Middle Kingdom in the second half of 17th century or some religious factors of the inner policy of the Society of Jesus. Lecture of the original authorial introductions to the published books of Michael Boym (i.e. Flora Sinensis and Clavis medica ) suggests the author found inspiration for his work in Jesuit motto „Omnia ad maiorem Dei gloriam”. By setting both religious and scientific targets to his works Boym persuaded the order authorities that his books should have been published.